2006
DOI: 10.1111/j.1469-7998.2006.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in ejaculate traits of the northern watersnake (Nerodia sipedon)

Abstract: Sperm competition occurs when the sperm of more than one male compete to fertilize the eggs of a female. In reptiles, sperm competition is particularly prevalent and is an important agent of sexual selection in males. Spermatogenesis in reptiles can be energetically expensive, suggesting that there may be costs to producing high-quality ejaculates. The northern watersnake Nerodia sipedon has a mating system characterized by aggregations in which a single female mates with multiple males, resulting in high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
0
21
1
2
Order By: Relevance
“…A second hypothesis is that sperm characteristics are condition‐dependent sexually selected traits (Rowe and Houle 1996). Condition‐dependence has indeed been found in sperm swimming speed and sperm length (Simmons and Kotiaho 2002, Malo et al 2005, Schulte‐Hostedde and Montgomerie 2006, García‐Gonzáles and Simmons 2007). However, we found no significant correlations between body condition and sperm characteristics, and even found that males with shorter tarsi produced sperm with higher overall velocity (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A second hypothesis is that sperm characteristics are condition‐dependent sexually selected traits (Rowe and Houle 1996). Condition‐dependence has indeed been found in sperm swimming speed and sperm length (Simmons and Kotiaho 2002, Malo et al 2005, Schulte‐Hostedde and Montgomerie 2006, García‐Gonzáles and Simmons 2007). However, we found no significant correlations between body condition and sperm characteristics, and even found that males with shorter tarsi produced sperm with higher overall velocity (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…To test whether male phenotype may signal sperm characteristics in the sand martin, we examined correlations between both sperm length and velocity and body measures and condition. As intra‐ejaculate variation in sperm morphology may be indicative of more or less stable spermatogenesis (Schulte‐Hostedde and Montgomerie 2006) we also tested the correlation between intra‐ejaculate variance (SD) in sperm length and body measures and condition.…”
mentioning
confidence: 99%
“…This assumption is untested in reptiles and its verification would require studies documenting that fertilization success in sperm competition is a heritable trait or that it is correlated with genetic quality more generally. No studies of the heritability of fertilization success exist in reptiles and there is also precious little evidence for intraspecific variation in sperm traits and their heritability (Schulte‐Hostedde & Montgomerie 2006; Uller et al . forthcoming).…”
mentioning
confidence: 99%
“…For example, strong stabilizing or directional selection would be expected to reduce additive genetic variance in traits under selection. A significant intraspecific variation in sperm morphometry has been documented in a wide range of taxa (e.g., Ward 1998; Morrow and Gage 2001; Schulte‐Hostedde and Millar 2004; Hettyey and Roberts 2006; Malo et al 2006; Minoretti and Baur 2006; Schulte‐Hostedde and Montgomerie 2006), but the causes of this variation are poorly understood (Ward 1998; Morrow and Gage 2001; Hettyey and Roberts 2006). This lack of knowledge is surprising given the considerable interest devoted to the evolutionary significance of sperm in sperm competition.…”
mentioning
confidence: 99%